Tinjauan Hukum Dan Kepatuhan Terhadap Good Corporate Governance Pada Perusahaan BUMN: Studi Kasus PT Asuransi Jiwasraya (Persero) - Tubagus Kudrat Kun; Elisatris Gultom (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The Good Corporate Governance in Insurance company of the state-owned company refers to the principles, regulations, and best practices in the insurance industry. The implementation of GCG put forward the principles which gives certainty in running the company. The purpose of this research is to analyze and review for legal and compliance aspect to the GCG in the insurance state-owned company. This research using normative-juridical method. The result of this research are some aspect in GCG implementation which is not correct thus resulting weak-based decision making and failed to protect the interest of stakeholders. Matters that faced by PT Asuransi Jiwasraya (Persero) becomes a landmark case for the ineffective and not correct GCG implementation on insurance state-owned company.